2013
DOI: 10.1074/jbc.m113.512384
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin Chaperone Activity Is Critical for Protein Homeostasis in Zinc-deficient Yeast*

Abstract: Background: Zinc is required as a structural cofactor for the folding of many proteins. Results: The chaperone activity of the Tsa1 peroxiredoxin is essential for protein homeostasis and growth of zinc-deficient yeast. Conclusion: Zinc limitation disrupts protein homeostasis, and cells need Tsa1 for tolerance. Significance: Disrupted protein homeostasis is a major and previously unrecognized stress of zinc deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 84 publications
(74 reference statements)
1
76
0
1
Order By: Relevance
“…Because intracellular conditions are highly reducing and Prx concentrations typically are much higher than the k d of decamerization, much of the cellular Prx will be in its chaperoneactivatable form, making posttranslational modifications likely unnecessary to achieve chaperone function in vivo. What appears to be necessary for chaperone activation of Prx, however, is a structural remodeling of the decameric structure, which can be induced by elevated temperatures (an inherent part of most in vitro chaperone assays) and possibly by low pH or other proteinunfolding stress conditions, such as oxidative stress (33). In conclusion, our data suggest that Prxs are capable of integrating different unfolding stimuli and translating them into structural rearrangements that trigger chaperone activation.…”
Section: Discussionmentioning
confidence: 79%
“…Because intracellular conditions are highly reducing and Prx concentrations typically are much higher than the k d of decamerization, much of the cellular Prx will be in its chaperoneactivatable form, making posttranslational modifications likely unnecessary to achieve chaperone function in vivo. What appears to be necessary for chaperone activation of Prx, however, is a structural remodeling of the decameric structure, which can be induced by elevated temperatures (an inherent part of most in vitro chaperone assays) and possibly by low pH or other proteinunfolding stress conditions, such as oxidative stress (33). In conclusion, our data suggest that Prxs are capable of integrating different unfolding stimuli and translating them into structural rearrangements that trigger chaperone activation.…”
Section: Discussionmentioning
confidence: 79%
“…Our initial studies indicated a role of the Tsa1 peroxidase activity in protecting zinc-deficient cells against an elevated level of reactive oxygen species in zinc-deficient cells. More recently, we found that the Tsa1 protein chaperone activity was more important than the peroxidase function for growth in zinc-deficient conditions (21). Zinc-deficient cells lacking Tsa1 chaperone activity accumulated elevated levels of stress-responsive protein chaperones, suggesting elevated unfolded protein accumulation and a corresponding heat shock response.…”
Section: Fet4mentioning
confidence: 99%
“…To test this hypothesis, we first analyzed the activity of the heat shockregulated transcription factor Hsf1, which responds to unfolded protein accumulation. Changes in Hsf1 activity in response to zinc status and UBI4 genotype were measured using a synthetic HSE-lacZ reporter gene (21). Reporter activity was strongly induced by a 1-h heat shock at 37°in both wildtype and ubi4⌬ zinc-replete cells (Fig.…”
Section: Reduction Of Proteasome Activity Suppresses the Ubi4⌬mentioning
confidence: 99%
“…In zinc-deficient conditions, however, atg41Δ 410 cells showed ~15-fold higher -galactosidase activity than in wild-type cells, indicating strong 411 activation of the SSA3 promoter. To confirm this phenotype, we used a second reporter with a 412 single heat shock element (HSE) inserted upstream of a basal promoter to drive expression of 413 lacZ (MACDIARMID et al 2013) and assayed -galactosidase activity in zinc-replete and 414 deficient wild-type and atg41Δ cells. This reporter also showed increased activity specifically in 415 zinc-limited atg41Δ mutants (Fig.…”
Section: Process 401 402mentioning
confidence: 99%
“…The 35 CTT1 catalase gene is also induced by Zap1 and this response is likely to eliminate the 36 oxidative stress that arises during zinc deficiency. The protein chaperones Hsp26 and Tsa1 37 are induced to deal with unfolded protein stress that might occur due to lack of this important 38 structural cofactor, and UBI4, encoding ubiquitin, is activated by Zap1 to maintain levels of this 39 critical stress protein (MACDIARMID et al 2013;MACDIARMID et al 2016). Thus, Zap1 plays 40 important roles in maintaining zinc homeostasis and adapting the cell to zinc-deficient growth.…”
Section: Introduction 21mentioning
confidence: 99%